Comparative study on effect of temperature & moisture on transformer insulation conductivity - Abdull Suleiman, Abubakar (2012)
It has been acknowledged that the insulation of the power transformers is the main cause of their failures. This can easily be attributed to the fact that all power transformers connected to electrical power networks bears loads and the load causes temperature rise and degradation of the cellulose paper. The by-product of the degradation includes moisture. The high temperature and moisture combine to accelerate the rate of insulation breakdown by increasing the material conductivity, σ and also increase the aging rate of the transformer. This paper has reviewed some transformer assessments and tests as sample data to study the effects of temperature and moisture on power transformer insulation conductivity. The results from the tests and measurements were analyzed and presented accordingly. The analyses of results found that irrespective of the assessment technique used, be it FDS, PDC or RVM, conductivity of the transformer insulating materials increases with any increase in both temperature and moisture content.